Inhibitory-based method for detection of Klebsiella pneumoniae carbapenemase Acinetobacter baumannii isolated from burn patients - Leila Azimi; Abdolaziz Rastegar Lari; Malihe Talebi; Parviz Owlia; Reza Alaghehbandan; Babak Asghari; Elnaz Rastegar Lari (Wolters Kluwer Medknow Publications, 2015)
Background: Klebsiella pneumoniae carbapenemase (KPC) is one of the carbapenemases that can cause multi-antibiotics resistance in Acinetobacter baumannii. A simple phenotypic rapid and accurate test for the detection of A. baumannii - KPC-producer can be useful in treating related infections. The aim of this study was to determine the synergism effect of boronic acid (BA), as an inhibitor, and meropenem to confirm modified Hodge test (MHT) positive strains for KPC-production. Materials and Methods: Totally, 126 A. baumannii isolates were used as clinical strains. Imipenem resistant isolates were identified by disk diffusion method according to the Clinical Laboratory Standards Institute recommendations. Presence of KPC in imipenem resistant isolates was determined using the MHT. In addition, we used BA as a KPC inhibitor for final confirmation of the species of interest. Additionally, we employed the use of synergism effect of meropenem and cloxacillin to detect false positive cases. Results: Of 126 strains, 108 were resistant to imipenem, for which 93 strains were MHT positive. Totally, 68 out of 93 MHT positive isolates had at least 5 mm enlargement of the diameter of the zone of growth inhibition between the meropenem alone and meropenem combined with BA. Of these 68 isolates, 8 had at least 5 mm enlargement of the diameter of the zone of growth inhibition with BA alone and in 60 strains it was observed by cloxacillin. Conclusion: Our study suggests that MHT alone cannot confirm KPC-producer microorganisms and that it requires other complementary tests such as the usage of inhibitors.